2014
DOI: 10.1371/journal.pone.0102832
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of the Carbohydrate Recognition Domain of Placental Protein 13 (PP13) in Pregnancy Evaluated with Recombinant PP13 and the DelT221 PP13 Variant

Abstract: IntroductionPlacental protein 13 (PP13), a placenta specific protein, is reduced in the first trimester of pregnancy in women who subsequently develop preeclampsia. A naturally occurring PP13 deletion of thymidine at position 221 (DelT221 or truncated variant) is associated with increased frequency of severe preeclampsia. In this study we compared the full length (wildtype) PP13 and the truncated variant.MethodsFull length PP13 or its DelT221 variant were cloned, expressed and purified from E-Coli. Both varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…Thereafter, blood pressure returned to normal over a period of several days such that there were no differences by day 15 of gestation. Although the mutant form of PP13 is unable to bind carbohydrates [32], this does not appear to be a requisite for inducing systemic hypotension. A former study by Burger et al [22] has shown that PP13 is capable of causing the release of prostacyclin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thereafter, blood pressure returned to normal over a period of several days such that there were no differences by day 15 of gestation. Although the mutant form of PP13 is unable to bind carbohydrates [32], this does not appear to be a requisite for inducing systemic hypotension. A former study by Burger et al [22] has shown that PP13 is capable of causing the release of prostacyclin.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the hypotensive effect, which was developed regardless of the wild-type or the mutated PP13 variant, the impact on placental and pup weights was not observed in the PP13M group, suggesting that carbohydrate binding was required, or that it was related to the anticipated altered tertiary structure of PP13M compared to the normal PP13 [32]. Furthermore, pup weights in this group were reduced by >50% on average by day 21 of pregnancy in the PP13M group compared to the other 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations